Microencapsulation of Bifidobacterium pseudocatenulatum G4 using natural matrices - Abdul Khalil, Khalilah (2012)
Probiotic cultures, nowadays, are widely used in food products for health enhancement. Low survivability of probiotic cultures in acidic environment such as in the stomach region has limited their potential benefits. The possibility of using encapsulation method to improve the survivability of probiotic bacterium, Bifidobacterium pseudocatenulatum G4 (G4), during passage through the gastrointestinal tract was investigated in this study. Bovine and fish gelatin with the combination of genipin (a plant extract) and sodium alginate were used as encapsulating matrices. The study was accomplished through the following approaches: 1) formulation of medium based on skim milk and yeast extract for development of active inoculum for G4 cultivation; 2) optimization of inoculum medium prior to subsequent fermentation, 3) optimization of the encapsulation matrices for improvement of encapsulation yield (%) and beads strength (g) before and after being exposed to simulated gastric (SGF) and intestinal fluids (SIF), and 4) determination of cell release activities based on swelling rate (%),release activity (OD), survival assay (cfumL-1) and beads morphology using scan electron microscope (SEM) during exposures to SGF and SIF. The use of 2 and 4% (w/v) skim milk as inoculum medium has elevated only 1 log cfumL-1 after 24 h of cultivation. Skim milk concentration ranging from 6 to 10% (w/v) greatly enhanced cell growth with more efficient carbon and free amino nitrogen usage as well as higher production of -galactosidase. Through statistical modeling based on the Face Centered Central Composite Design (FCCD), the optimum concentration of combined skim milk and yeast extract was determined as 7.02 and 1.73% (w/v), respectively. A validation experiment proved that the predicted and experimented values were not significantly different (p > 0.05). Substantial improvement in biomass production (11.72 cfumL-1) was achieved in cultivation with optimized medium in 2-L stirred tank bioreactor for 18 h, and this biomass production was not statistically different (p > 0.05) as compared to the cultivation using commercial inoculum medium. FCCD was also employed for the optimization of encapsulating matrices. The optimum concentration for bovine gelatin-genipin-alginate was predicted at 11.21% (w/v), 13.96 mM and 2.60% (w/v), respectively. While, in the case of fish gelatin-genipin-alginate, combined matrices at 12.57% (w/v), 19.12 mM and 5% (w/v) was predicted to generate optimum responses. Upon verification, experimental data of bovine gelatin-genipin-alginate and fish gelatin-genipinalginate remained close value to the predicted data with low error for all the responses. As compared to porcine-genipin-alginate encapsulating matrices, the optimized bovine and fish gelatin-genipin-alginate have both demonstrated lower strength (p < 0.05) after SIF exposure. The performances of the optimized bovine gelatin-genipin-alginate and fish gelatin-genipin-alginate in protecting G4 and other probiotics were also determined. Eight groups of encapsulating matrices were evaluated: 1) optimized bovine gelatin-genipin-alginate, 2) optimized fish gelatin-genipin-alginate, 3) porcine gelatin-genipin-alginate, 4) optimized bovine gelatin-alginate, 5) optimized fish gelatin-alginate, 6) porcine gelatin-alginate, 7) alginate alone, 8)free cell (unencapsulate). Low encapsulation yield was observed in groups 2 and 5, respectively. Meanwhile group 1 showed highest in encapsulation yield. Slow swelling rate during the SGF exposure was shown by group 1, 3, 4 and 6 while groups 5 was demonstrated progressive swelling and slightly erode at 120 min of exposure. The releases of cells occur when the beads disintegrate and these were observed through the cells release activity analysis. All groups were presented positive performance in releasing cells into the intestinal region with higher optical density and lower survivability of entrapped cells obtained under SIF exposure except for groups 3 and 6, respectively. Factors like gelatin source, bloom strength and the presence of alginate played important roles in stabilizing the chemical cross link of the gelatin especially in acidic environment. Encapsulations of both bovine and fish gelatin with genipin and alginate combinations have successfully improved the survival and cells release and this approach could potentially be useful in replacing porcine gelatin for the delivery of probiotic culture to the target area in the intestinal region.